Implementation of the Use of an Annuity Calculator Application for Grade XII Students at Sekolah Khusus Islam Terpadu Yarfin - Utomo, Satrio Budi; Kurnia, Oki (Sean Institute, 2026)
Learning social arithmetic, particularly annuities, requires both conceptual understanding and procedural accuracy. For students with visual impairments, these demands are often intensified due to limited access to visual mathematical notation and multi-step calculations. This study aims to describe the implementation of a Windows-based annuity calculator application in teaching annuity concepts to Grade XII students with visual impairments at Sekolah Khusus Islam Terpadu Yarfin, as well as to identify its benefits and challenges. Using a descriptive case study approach, data were collected through classroom observations, semi-structured interviews with teachers and students, documentation analysis, and pretest–posttest assessments. The findings indicate that the application supports students’ conceptual understanding by reducing procedural calculation burdens and enhances learning independence when operated via keyboard and screen reader. Challenges include varying ICT literacy levels, interface accessibility issues, and limited device availability. The study highlights the importance of integrating accessible assistive technology with appropriate pedagogical strategies to support inclusive mathematics learning.